Challenges in smart spaces: aware of users, preferences, behaviours and habits - Oliveira, Pedro Filipe (2018)
There are new opportunities for research in the field of smart environments that should be explored. The concepts of smart homes and home automation, are currently in growing expansion in the scientific and research point of view, as the market demands for better solutions in this field. Users want that those spaces smartly adapt to their preferences in a transparent way. This paper describes the process of planning, reasoning and modeling of a Smart Environment, using emerging wearable devices on the market (smart watches, fitness trackers, etc.) and newer technologies like NFC, BLE and Wi-Fi Direct. Enabling the user to optimize the efficiency, comfort, and safety at the environments.